2012
DOI: 10.1080/00981389.2012.657296
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Community Health Workers in Providing Outreach and Education for Colorectal Cancer Screening in Appalachian Kentucky

Abstract: The purpose of this study was to examine the effectiveness of a community health worker (CHW)-delivered cancer education program designed to increase knowledge and awareness of colorectal cancer screening options. The study population was an extremely vulnerable and medically underserved geographic region in Appalachian Kentucky. CHWs enrolled participants in face-to-face visits, obtained informed consent, and administered a baseline assessment of knowledge of colorectal cancer risks and the benefits of screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 21 publications
(21 reference statements)
3
26
0
Order By: Relevance
“…The PNs were very successful enrolling women for the study, indicating a capacity to interact effectively with this vulnerable population, which is consistent with previous research (Braun et al, 2012; Cohen et al, 2013; Dohan & Schrag, 2005; Feltner et al, 2012). Of those eligible, the enrollment rate was nearly 80%.…”
Section: Discussionsupporting
confidence: 88%
“…The PNs were very successful enrolling women for the study, indicating a capacity to interact effectively with this vulnerable population, which is consistent with previous research (Braun et al, 2012; Cohen et al, 2013; Dohan & Schrag, 2005; Feltner et al, 2012). Of those eligible, the enrollment rate was nearly 80%.…”
Section: Discussionsupporting
confidence: 88%
“…(Bravata, Ho, Meehan, Brass, & Concato, 2007; Demaerschalk, et al, 2010; Fonarow et al, 2012; Lichtman, Leifheit-Limson, Jones, Wang, & Goldstein, 2013) Research examining care coordination for people with cancer and stroke demonstrate a shift from utilization of more costly specialists and hospital care to more efficient primary care with reduced hospitalizations. (Claiborne, 2006; Feltner, et al, 2012; Ramsey, et al, 2009) The results from the KC 3 T program agree with these findings, in that the use of the a specially trained CHW as the KC 3 T navigator was able to shift visits from the ED to the primary care physician and there was only one 30-day readmission, which was not stroke related.…”
Section: Discussionsupporting
confidence: 70%
“…(Feltner, Ely, Whitler, Gross, & Dignan, 2012; Ramsey et al, 2009) Researchers have recently examined the effectiveness of utilizing allied health professionals (PT, OT, or nurses) to support access to services. (Dewan, et al, 2014; Egan, et al, 2010; Poston, et al, 2014) While these previous studies using healthcare professionals have demonstrated a decrease in 30-day readmission rates, they were significantly more costly to provide due to salary requirements and are did not employee navigators from the local communities.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the disparity in outcome due to Race/% college graduate of County in relation to receipt of post-operative radiation treatment. Lack of radiotherapy has been shown to be associated with inferior outcomes as shown in other studies (Dragun et al, 2012;Feltner et al, 2012;Yao et al, 2012). We found that the breast cancer patients lived in less educated counties were at a disadvantage in terms of cause specific survival.…”
Section: Discussionsupporting
confidence: 62%